Rancang Bangun Sistem Informasi Akademik Berbasis Web pada SMP PGRI 363 Pondok Petir - Muhammad Yunus Rangkuti; Vayza Valensia Gabrella Wuntu (Jurnal Riset Informatika dan Inovasi, 2026)
The utilization of information technology in the education sector has become an essential requirement to improve the efficiency of academic data management. Web-based academic information systems have been widely developed to assist schools in managing student data, teacher data, subjects, and examination scores in an integrated manner (Ira Zulfa et al., 2023). SMP PGRI 363 previously experienced difficulties in managing academic data due to manual processes, which potentially caused data inaccuracies and delays in information delivery. This study aims to design and develop a web-based academic information system at SMP PGRI 363 to enhance administrative efficiency and student assessment processes. The system was developed using PHP as the programming language and MySQL as the database management system, implementing a multi-user concept. The Rapid Application Development (RAD) method was applied to accelerate system development and involve users during the development process (Lukman Santoso et al., 2022).The results of this study indicate that the developed academic information system is capable of managing academic data in a structured manner and supporting a more efficient and accurate student assessment process. Therefore, the system is expected to improve the quality of academic management in schools, particularly in terms of assessment efficiency (Richard Martin et al., 2025).